TINDAK TUTUR ILOKUSI DALAM PIDATO GUBERNUR KALIMANTAN BARAT PERIODE 2018—2023 - Yulianti Yulianti; Ahmad Rabi’ul Muzammil; Agus Syahrani (Universitas Tanjungpura, 2021)
AbstractThe problem in this research is what kinds of illocutionary speech acts appear in H. Sutarmidji, SH, M.Hum's speech. Governor of West Kalimantan for the period 2018-2023 and what are the functions of the types of illocutionary speech acts that appeared in the speech of H. Sutarmidji, SH, M.Hum. Governor of West Kalimantan for the period 2018-2023. This research is in the form of a qualitative descriptive method. The results showed that the illocutionary speech act data used in H. Sutarmidji, SH, M.Hum's speech. The governor of West Kalimantan for the period 2018-2023, there were 136 speeches consisting of 40 assertive illocutionary speech acts, 52 directive illocutionary speech acts, 32 expressive illocutionary speech acts, 18 commissive illocutionary speech acts, and 3 declarative illocutionary speech acts, with The function details are as follows: declare 4 speeches, inform 33 speeches, report 1 speech, receive 1 speech, boast 1 speech, order 24 speeches, order 10 speeches, suggest 5 speeches, advise 10 speeches, demand 3 speeches, acknowledge 1 thank you 6 utterances, apologize for 3 speeches, utter 3 utterances, criticize (criticize) 21 utterances, say 10 prayers, swear 1 utterance, threaten 6 utterances, sentence 3 utterances.Keywords: Speech Actions, Illocution, Speech